Advances in Superplasticity from a Laboratory Curiosity to the Development of a Superplastic Forming Industry - Jittraporn Wongsa-Ngam; Terence G. Langdon (My University, 2022)
Superplasticity refers to the ability of some materials to pull out to tensile elongations of 400% or more when the strain rate sensitivity is ~0.5. The first report of true superplastic flow was published in 1934 in experiments conducted in England. However, this remarkable result attracted little interest among western scientific researchers and the result remained a laboratory curiosity for many years. Later, following extensive research on superplasticity in the Soviet Union, interest developed in the west, and superplasticity became a topic of extensive scientific research. This research was further enhanced with the demonstration that the application of severe plastic deformation provided an opportunity for achieving grain refinement to the submicrometer or even the nanometer level, and these small grains were especially attractive for achieving good superplastic properties. It is now recognized that superplastic alloys provide an excellent forming capability, especially in making high quality curved parts that are not easily fabricated using more conventional processes. This has led to the development of a large superplastic forming industry that currently processes many thousands of tons of sheet metals. This report traces these developments with an emphasis on the scientific principles behind the occurrence of superplastic flow.
Keywords: Superplasticity; Microstructure and mechanical properties